The Queen's People : A Study of Hegemony, Coercion, and Accommodation among the Okanagan of Canada - Carstens, Peter (Book collections on Project MUSE., 1991)
An analysis of the realities of everyday life for Okanagan Indians on a reserve near Vernon. Carstens applies the peasant model to the study of reserve systems and finds significant correlations. Questions of class, status, power, and institutionalized inequality also come into play.